Ten new Gammarus species (Crustacea: Amphipoda: Gammaridae) from Yunnan-Guizhou Plateau, China - Hou, Zhonge; Li, Junbo; Li, Shuqiang (Zootaxa, 2013)
Ten new species of the genus Gammarus are described from Yunnan-Guizhou Plateau, Southwest China, including Gammarus amabilis sp. nov., G. citatus sp. nov., G. echinatus sp. nov., G. egregius sp. nov., G. eliquatus sp. nov., G. hirtellussp. nov., G. margcomosus sp. nov., G. rivalis sp. nov., G. silendus sp. nov. and G. tranquillus sp. nov. Four of them are stygobite and with no eyes. Detailed illustrations and comparisons with related species are presented. A key to all species from Yunnan-Guizhou Plateau are given.